Semi-empirical description of quenching processes in a track of ionizing particles for organic crystalline scintillators - Galunov, N.Z.; Martynenko, E.V. (Functional Materials, 2008)
The semi-empirical description of the process of quenching in the track that takes into account the influence of polarization of molecules in the track by charge states is proposed. The values of light yield were measured for alpha-, neutron- and gamma-excitation of d25mmx20mm stilbene single crystal and the d30mmx20mm composite scintillators on the base of stilbene (unary system), and p-terphenyl doped by 0.1% 1,4-diphenylbutadiene-1,3 of (binary system). The description obtained is in a good agreement with results of light yield experimental data. Пропонується напівемпіричний опис процесу гасіння у треку, який враховує можливість ефекту поляризації зарядовими станами молекул у треку. Для монокристала стильбену d25ммx20мм та композиційних сцинтиляторів d30ммx20мм на основі стильбену (однокомпонентна система) та п-терфенілу, активованого 0.1% 1,4-дифенілбутадієном-1,3 (двокомпонентна система) виміряно величини світлового виходу при альфа-, нейтронному- та гамма-збудженні. Отриманий опис добре узгоджується із експериментальними результатами для світлового виходу. Предлагается полуэмпирическое описание процесса тушения в треке, учитывающее возможность эффекта поляризации зарядовыми состояниями молекул в треке. Для монокристалла стильбена d25ммx20мм и композиционных сцинтилляторов d30ммx20мм на основе стильбена (однокомпонентная система) и п-терфенила, активированного 0.1% 1,4-дифенилбутадиеном-1,3 (двухкомпонентная система) измерены величины светового выхода при альфа-, нейтронном- и гамма- возбуждении. Полученное описание хорошо согласуется с экспериментальными данными по световому выходу.